1940
DOI: 10.1021/ie50362a013
|View full text |Cite
|
Sign up to set email alerts
|

Detergents from Kerosene

Abstract: Sodium alkyl sulfates have been prepared from kerosene and have been compared with similar commercial compounds of known structure by means of a foam test and an interfacial tension test. The sodium alkyl sulfates have been prepared from all of the straight-chain dodecanols and similarly tested. The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

1940
1940
1971
1971

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 5 publications
1
5
0
Order By: Relevance
“…A careful study of Figures 1 and 2 shows that laurylamine hydrochloride is comparable to sodium lauryl sulfate by the drop number test, but that all of the other amine salts are notably less satisfactory for foam-producing agents and general detergents as measured by these tests. This is in agreement with the results obtained on the corresponding sodium alkyl sulfates (7) if it be conceded that most of these derivatives are of the secondary type. Since there are twenty secondary hydrogen groupings to six primary hydrogen groupings in dodecane, secondary derivatives certainly represent the principal products.…”
Section: Aluessupporting
confidence: 92%
See 3 more Smart Citations
“…A careful study of Figures 1 and 2 shows that laurylamine hydrochloride is comparable to sodium lauryl sulfate by the drop number test, but that all of the other amine salts are notably less satisfactory for foam-producing agents and general detergents as measured by these tests. This is in agreement with the results obtained on the corresponding sodium alkyl sulfates (7) if it be conceded that most of these derivatives are of the secondary type. Since there are twenty secondary hydrogen groupings to six primary hydrogen groupings in dodecane, secondary derivatives certainly represent the principal products.…”
Section: Aluessupporting
confidence: 92%
“…(6) Jayme, G., and Steinmann, R., Ibid., 35, 337-64T (1937). (7) Noll, A., Ibid., 29, 114-16T (1931). (8) Rys, L" Ibid., 29, 325T (1931).…”
Section: Preferential Adsorption Of Alkalimentioning
confidence: 99%
See 2 more Smart Citations
“…However, the solubility of this saturated material is likely to be poorer than that of ricinoleyl sulfate. Several investigations (5,10) have shown that when the hydrophobic chain is excessively branched, the wetting activity is greatly enhanced. In ricinoleyl sulfate almost all the linkages in the chain are capable of free rotation.…”
Section: Discussionmentioning
confidence: 99%